DETERMINASI PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM (Jurnal Riset Akuntansi, 2022)
The purpose of the study is to determine the magnitude of the effect of Profitability on stock prices and the amount of liquidity influence on stock prices in property companies. Real estate stock price fluctuations were caused by negative sentiment, rising interest rates, low demand for stock prices, and the fall in the rupiah exchange rate against the UNITED STATES dollar, so that real estate, property, and building construction sub-sector companies experienced a decline in the company's performance. The research method used is a verificative descriptive analysis method. The population, namely sub-sector companies such as real estate, property, and building construction recorded on the IDX for the 2016-2018 period, includes 11 companies using samples in the form of purpose sampling. The sample in the form of financial statements in the company's quarter was 45 samples of financial statements for 3 periods from 2016-2018. The dependent variables are stock prices, while the independent variables in this study are ROA (Return On Asset) and CR (Current Ratio). The technical data analysis used is multiple linear regression analysis and is assisted by the SPSS version 20 application program. The results showed that Return On Asset (ROA) had a significant effect on stock prices with a positive relationship and Current Ratio (CR) had a significant effect on stock prices with a positive relationship. Keywords: Return On Asset, Current Ratio, Stock Price